2017
DOI: 10.2147/copd.s140043
|View full text |Cite
|
Sign up to set email alerts
|

Spreading improvements for advanced COPD care through a Canadian Collaborative

Abstract: BackgroundA year-long pan-Canadian quality improvement collaborative (QIC) led by the Canadian Foundation for Healthcare Improvement (CFHI) supported the spread of the successful Halifax, Nova Scotia-based INSPIRED COPD Outreach Program™ to 19 teams in the 10 Canadian provinces. We describe QIC results, addressing two main questions: 1) Can the results of the Nova Scotia INSPIRED model be replicated elsewhere in Canada? 2) How did the teams implement and evaluate their versions of the INSPIRED program?MethodsC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
(32 reference statements)
2
19
0
Order By: Relevance
“…It aims to achieve a proactive attitude towards their pathology, but its influence on clinical results has not been sufficiently investigated. This study has found that our educational program is similar in terms of educational results to programs carried out in other countries such as Canada or Sweden; 11 13 despite the fact that patients included in our study, had a recent diagnosis and had not received information previously about their disease. The domains of the questionnaire in which patients have the greatest IN are “Diet” and “Self-care”.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It aims to achieve a proactive attitude towards their pathology, but its influence on clinical results has not been sufficiently investigated. This study has found that our educational program is similar in terms of educational results to programs carried out in other countries such as Canada or Sweden; 11 13 despite the fact that patients included in our study, had a recent diagnosis and had not received information previously about their disease. The domains of the questionnaire in which patients have the greatest IN are “Diet” and “Self-care”.…”
Section: Discussionsupporting
confidence: 61%
“…The Lung Information Needs Questionnaire (LINQ) 9 is a self-administered questionnaire consisting of 16 questions divided into 6 domains: Knowledge about the disease, medications, self-management, exercise, diet and smoking. It has been used to evaluate respiratory rehabilitation programs, 10 in other types of educational programs for patients with COPD in outpatient clinics 11 , 12 or during hospital admissions. 13 This questionnaire has been previously validated 9 and translated into several languages including Spanish.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of novel services include: patient-centred medical homes [37], breathlessness services that provide early access to palliative care [38, 39], and an Advanced Lung Disease Service [40]. Within Canada, the INSPIRED COPD Outreach Program TM [41] and the subsequent pan-Canadian care collaborative [42] reported rapid changes to work practices, cultural change, and skills sets at relatively low cost. Common to these new programs is an interdisciplinary approach.…”
Section: Introductionmentioning
confidence: 99%
“…This national dissemination program was launched in September 2014 by the Canadian Foundation for Healthcare Improvement (CFHI) with support from Boehringer Ingelheim (Canada) Ltd., and engaged 19 healthcare teams across Canada. Two prior publications describe experiences of participating in the program and in the spread of the INSPIRED approach [24,25]. Building on these results and to address existing knowledge gaps, we examined role clarification in the INSPIRED COPD Collaborative to investigate two questions: i) how does the spread of QI initiatives impact role clarification, and ii) how does role clarity develop between hospital and community health organizations working together to transition patients from one system of care to another?…”
Section: Introductionmentioning
confidence: 99%